Optimization of xylose production from sugarcane bagasse using response surface methodology (RSM) - Nurul Izwanie, Rasli (2010)
Xylose is a monosaccharide containing five carbon atoms, including an aldehyde functional group. It is a pentose sugar which has chemical formula C5H10O5. Hemicellulose is present in plant cell walls and is associated with the cellulose. Its chemical formula is (C5H8O4)n and in some cases is (C6H10O5)n. It is possible to hydrolyze hemicellulose by several processes (enzymatic, physical and chemical) for producing monomer sugars with great purity and high yield. The aim of this study is to optimize the xylose production from sugarcane bagasse by manipulating the temperature, agitation rate and enzyme concentration using Response Surface Methodology (RSM) based on central composite design (CCD). In this study, producing xylose from sugarcane bagasse contributes to reduce the environmental impact and bioprocess cost. Alkaline and acid hydrolysis method was used for the pretreatment of sugarcane bagasse. After the pretreatment, the screening process was constructed to determine the best range of parameters to be used in optimization process. Seventeen experiments have been arranged by RSM for optimization. The optimized conditions of parameters were 50°C of temperature, 180 rpm of agitation rate and 2 mg/ml of enzyme concentration with the predicted xylose production was 0.367 mg/ml. The actual xylose production was 0.373 mg/ml. Before the optimization, the xylose production was 0.228 mg/ml. As a conclusion, the optimization of xylose production from sugarcane bagasse by using RSM was successfully done with 63.6% of increment.